D’Cika Building Customer Satisfaction Through Superior Service Quality - Fitri, Sofianah; Supendi, Moh (Universitas Muhammadiyah Jakarta, 2024)
This study examines the impact of service quality on customer satisfaction at D'Cika Jatimakmur. D'Cika's service needs improvement because only a few customers are satisfied. The store needs optimal service to maintain a positive reputation. This research uses the Lemeshow formula to obtain a sample size of 100 respondents. The sampling technique of this study was non-probability purposive sampling. The researchers distributed questionnaires to customers of D'Cika, with the respondents identified as those who had made at least one cake purchase. The data collected is then processed and analyzed using the SPSS 25. The findings of this study indicate that service quality has a positive and significant effect on customer satisfaction. Specifically, the results of the simple regression analysis indicate that the constant coefficient value is 2.077, and the independent variable is 0.487. These results indicate that when the service quality (X) is at its lowest level, customer satisfaction (Y) is positive by 2.077. The R square test yielded a value of 0.547, indicating that service quality significantly influences customer satisfaction. The results of the T-test indicate a significance value of 0.000, which is less than 0.05. Consequently, the researcher concludes that alternative hypothesis (Ha), which states that there is a positive and significant influence between service quality and customer satisfaction at D'Cika, is accepted.